Nipah Virus: A Comprehensive Review - Patel, Dr. Megha (Asian Journal of Pharmaceutics (AJP), 2025)
The Nipah virus (NiV), an emerging zoonotic pathogen from the Henipavirus genus, is known to cause severe respiratory infections and encephalitis in humans. Since its first discovery in 1998 during an epidemic in Malaysia, NiV has repeatedly produced outbreaks in Bangladesh and India, often resulting in high fatality rates. Pteropus fruit bats serve as the primary natural reservoir for human transmission, which can occur through direct contact, contaminated food, or contact with diseased animals. Clinical symptoms vary widely, ranging from mild febrile illness to fatal encephalitis. Laboratory confirmation is achieved through molecular methods like reverse transcriptase polymerase chain reaction and serological assays. Despite the lack of licensed treatments or vaccines, several therapeutic candidates such as ribavirin, favipiravir, monoclonal antibodies, and remdesivir have demonstrated varying levels of efficacy in preclinical studies. Public health interventions, including surveillance, outbreak containment, and minimizing exposure to natural reservoirs, remain essential. Given its epidemic potential and lack of specific therapies, NiV has been designated a priority pathogen by the World Health Organization. Continued research and coordinated global efforts are critical to develop effective prevention and management strategies